The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1007/s11033-010-0283-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis and heavy metal detoxification of ABCC1/MRP1 in zebrafish

Abstract: ABCC1/MRP1 belongs to the ATP-binding cassette superfamily and its elevated expression is closely associated with the multidrug resistance of various tumor cells. In normal tissues, ABCC1 confers resistance to a wide variety of xenobiotics and toxicants, demonstrating its important roles in tissue defense. Here, we report the cloning and functional characterization of abcc1 gene in zebrafish. This gene is localized on zebrafish chromosome 3 and contains a 4,557 bp open-reading frame. The deduced polypeptide is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 37 publications
3
44
0
2
Order By: Relevance
“…So far, functions of MRP subfamily proteins in aquatic organisms are well characterized. Our previous studies have revealed that zebrafish Abcc1 (Long et al, 2011a), Abcc2 (Long et al, 2011d) and Abcc5 (Long et al, 2011b) play vital roles in efficient detoxification of heavy metals. Zebrafish Abcb4 has been demonstrated to function as a cellular toxicant transporter, which can extrude a variety of toxic compounds including galaxolide, tonalide and phenanthrene (Fischer et al, 2013), so it may play an important role in cellular protection against xenobiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, functions of MRP subfamily proteins in aquatic organisms are well characterized. Our previous studies have revealed that zebrafish Abcc1 (Long et al, 2011a), Abcc2 (Long et al, 2011d) and Abcc5 (Long et al, 2011b) play vital roles in efficient detoxification of heavy metals. Zebrafish Abcb4 has been demonstrated to function as a cellular toxicant transporter, which can extrude a variety of toxic compounds including galaxolide, tonalide and phenanthrene (Fischer et al, 2013), so it may play an important role in cellular protection against xenobiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Collection of eggs and culture of embryos were performed as in our previous study (Long et al, 2011a;Gu et al, 2013). Embryos were staged according to hour post-fertilization (hpf).…”
Section: Zebrafish Maintenance and Mc-lr Treatmentsmentioning
confidence: 99%
“…The ubiquitous nature of arsenic in the environment has led to the evolution of arsenic adaptation mechanisms from bacteria to humans (Rosen and Liu, 2009). Members of the ABC transporter superfamily subfamily "C" have been shown to be critical for protecting many organisms from arsenic, including Saccharomyces cerevisiae, Leishmania, Arabidopsis, Caenorhabditis elegans, and Danio rerio (Broeks et al, 1996;Dey et al, 1996;Ghosh et al, 1999;Long et al, 2011;Song et al, 2010). In all of these organisms, ABCC proteins detoxify arsenic either by extrusion from cells or through sequestration within intracellular organelles as thiol conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…The tagged zebrafish abcc2 was then subcloned into the pRc/CMV2 expression vector at the HindIII and XbaI sites to generate the pRc/CMV2-ABCC2-Flag. The pRc/CMV2-EGFP generated in our previous study (Long et al, 2010a) was used as a control in functional characterization of zebrafish ABCC2.…”
Section: Cloning Of Zebrafish Abcc2 Cdna and Generation Of Constructsmentioning
confidence: 99%
“…However, most of MRP transporters in zebrafish are yet to be characterized and little is known about their physiological functions in development and detoxification of toxicants including toxic heavy metals. In our previous studies, we demonstrated the potential functions of zebrafish ABCC1 and ABCC5 in heavy metal detoxification (Long et al, 2010a;Long et al, 2011), and found that the up-regulation of zebrafish ABCC2 may be involved in the heavy metal resistance of ZF4-Cd cells selected by chronic cadmium exposure (Long et al, 2010b). In this study, we cloned the abcc2 cDNA from zebrafish, investigated its developmental and tissue-specific expression, transcriptional responses to heavy metals, and evaluated its roles in cellular efflux of heavy metals such as cadmium, mercury and lead.…”
Section: Introductionmentioning
confidence: 98%